KRAS Protein Stability Is Regulated through SMURF2: UBCH5 Complex-Mediated β-TrCP1 Degradation - Shirish Shukla; Uday Sankar Allam; Aarif Ahsan; Guoan Chen; Pranathi Meda Krishnamurthy; Katherine Marsh; Matthew Rumschlag; Sunita Shankar; Christopher Whitehead; Matthew Schipper; Venkatesha Basrur; Daniel R. Southworth; et al. (Neoplasia: An International Journal for Oncology Research, 2014)
Attempts to target mutant KRAS have been unsuccessful. Here, we report the identification of Smad ubiquitination regulatory factor 2 (SMURF2) and UBCH5 as a critical E3:E2 complex maintaining KRAS protein stability. Loss of SMURF2 either by small interfering RNA/short hairpin RNA (siRNA/shRNA) or by overexpression of a catalytically inactive mutant causes KRAS degradation, whereas overexpression of wild-type SMURF2 enhances KRAS stability. Importantly, mutant KRAS is more susceptible to SMURF2 loss where protein half-life decreases from >12 hours in control siRNA-treated cells to <3 hours on Smurf2 silencing, whereas only marginal differences were noted for wild-type protein. This loss of mutant KRAS could be rescued by overexpressing a siRNA-resistant wild-type SMURF2. Our data further show that SMURF2 monoubiquitinates UBCH5 at lysine 144 to form an active complex required for efficient degradation of a RAS-family E3, β-transducing repeat containing protein 1 (β-TrCP1). Conversely, β-TrCP1 is accumulated on SMURF2 loss, leading to increased KRAS degradation. Therefore, as expected, β-TrCP1 knockdown following Smurf2 siRNA treatment rescues mutant KRAS loss. Further, we identify two conserved proline (P) residues in UBCH5 critical for SMURF2 interaction; mutation of either of these P to alanine also destabilizes KRAS. As a proof of principle, we demonstrate that Smurf2 silencing reduces the clonogenic survival in vitro and prolongs tumor latency in vivo in cancer cells including mutant KRAS-driven tumors. Taken together, we show that SMURF2:UBCH5 complex is critical in maintaining KRAS protein stability and propose that targeting such complex may be a unique strategy to degrade mutant KRAS to kill cancer cells.